2020
DOI: 10.1111/jocn.15543
|View full text |Cite
|
Sign up to set email alerts
|

To what extent Unfinished Nursing Care tools coincide with the discrete elements of The Fundamentals of Care Framework? A comparative analysis based on a systematic review

Abstract: Aims and objectives To establish whether, and to what extent, tools measuring Unfinished Nursing Care (UNC) that have been validated to date have the ability to detect the discrete elements of the ‘Integration of care’ dimension of The Fundamentals of Care Framework (The Framework). Background UNC and The Framework have been established as two separate research lines, focused on (a) omitted care and related tools, and (b) on how to improve patient care, respectively. However, no attempts have been made to date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Attributes are described as the key aspects that describe a given concept (Rodgers, 2000). Based on our search, fundamentals of care could be described as a multidimensional and multifaceted phenomenon (Feo, Donnelly, et al, 2018) of nursing activities (Palese et al, 2021; Rey et al, 2020) based on patient and family centred care needs (Aspinall et al, 2020; Avallin et al, 2018; Jeffs et al, 2018; Pene et al, 2021; van Belle et al, 2020; Zwakhalen et al, 2018). The fundamentals of care are holistic (Avallin et al, 2018; Jackson & Kozlowska, 2018; Meehan et al, 2018), compassionate (Feo, Donnelly, et al, 2018; Jeffs et al, 2018), invisible, complex nursing activities (Parr et al, 2018) and yet they are straightforward for nurses to carry out (Feo et al, 2019; Feo, Donnelly, et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Attributes are described as the key aspects that describe a given concept (Rodgers, 2000). Based on our search, fundamentals of care could be described as a multidimensional and multifaceted phenomenon (Feo, Donnelly, et al, 2018) of nursing activities (Palese et al, 2021; Rey et al, 2020) based on patient and family centred care needs (Aspinall et al, 2020; Avallin et al, 2018; Jeffs et al, 2018; Pene et al, 2021; van Belle et al, 2020; Zwakhalen et al, 2018). The fundamentals of care are holistic (Avallin et al, 2018; Jackson & Kozlowska, 2018; Meehan et al, 2018), compassionate (Feo, Donnelly, et al, 2018; Jeffs et al, 2018), invisible, complex nursing activities (Parr et al, 2018) and yet they are straightforward for nurses to carry out (Feo et al, 2019; Feo, Donnelly, et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The fundamentals of care are holistic (Avallin et al, 2018; Jackson & Kozlowska, 2018; Meehan et al, 2018), compassionate (Feo, Donnelly, et al, 2018; Jeffs et al, 2018), invisible, complex nursing activities (Parr et al, 2018) and yet they are straightforward for nurses to carry out (Feo et al, 2019; Feo, Donnelly, et al, 2018). These different aspects were already expressed in the Fundamentals of Care Framework (Mudd et al, 2020; Palese et al, 2021; Voldbjerg et al, 2018) that was described by Kitson (2018) and identified as below. The centre of this framework is the relationship between nurse and patient based on trust (Aspinall et al, 2020; Feo, Donnelly, et al, 2018; Hansen & Jørgensen, 2020; Jeffs et al, 2018; Kitson, Dow, et al, 2013; Kitson, Robertson‐Malt, & Conroy, 2013; Meehan et al, 2018; Pavedahl et al, 2021; Pene et al, 2021; Pinero de Plaza et al, 2021) to establish a continued interaction; the 12 basic needs (Table 1) focus on the patient's physical care needs (nutrition and hydration, personal hygiene and physical comfort) (Feo, Donnelly, et al, 2018; Feo, Kitson, & Conroy, 2018; Kitson et al, 2010; Lillekroken, 2019; Vollman, 2009), and on the attention by the nurse for the patient's psychological and emotional needs (Kitson, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the Framework can be reliably estimated and its variables are predictive of the integration of the care dimension. One previous study has attempted to hierarchically link the interaction of all the Framework variables together, but was unable to validate those factors or show a causal link between them and the context of care factors (Palease et al, 2021). This current study has also shown that the Framework is indeed a multi‐dimensional construct and reflects the inter‐relationships between the contexts of care variables and the integration of care variables.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with unmet needs are more likely to experience poor quality of life (Bagnasco et al, 2019). The overlap between the terminology used to describe the various aspects of missed care / poor‐quality fundamental care (e.g., missed care, care left undone, implicitly rationed care, unfinished nursing care, unmet needs) has been explored elsewhere (Jones et al, 2015; Palese et al, 2021; Willis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%